RESPONS PERTUMBUHAN DAN HASIL KEMBANG KOL(Brassica oleracea, L var. botrytis) DATARAN RENDAH TERHADAP SISTEM BUDIDAYA PADA LAHAN PODZOLIK - Nurlianti Pertiwi; Ejo Imandeka (University of Prof. Dr. Hazairin, SH, 2019)
The aim of this research is to examine the response of lowland Cauliflower plants cultivated in PMK land using bokhasi palm fronds as an effort to improve PMK land. Another goal is to reduce the use of chemical fertilizers in Cauliflower cultivation so that it is expected to reduce production costs. The study was conducted in Pintu Batu sub-district, Teluk Segara sub-district, Bengkulu city with a height above sea level of 10 m, in May to August 2018 the method used was a one-factor Randomized Completely Block Design (RCBD) with 3 replications. The treatments given consisted of 3 systems namely organic cultivation, semi-organic cultivation, and conventional cultivation. The results showed a significant effect of the cultivation system treatment on the growth and yield of Cauliflower plants. Conventional and semi-organic and organic cultivation show significant differences in the growth variable, which are leaf area and wet weights and yield variables, ie crop wet weight. The average crop weight obtained in conventional cultivation is 416 g / plant significantly different from the crop weight produced in semi-organic cultivation is 243 g / plant. Semi-organic cultivation of plant growth is not uniform compared to conventional cultivation which is relatively uniform so that harvest time can be done more than once.